PROTEIN PROFILES OF IN VITRO AND IN VIVO HALOTOLERANT RHIZOBIUM SPECIES ISOLATED FROM CAJANUS CAJAN PLANT. - R.C.SHENDE; M.B. PATIL (International Journal of Pharma and Bio Sciences, 2012)
Salinity-induced changes in the protein profiles in Rhizobium sp. exhibited alterations in proteins, which either showed an enhanced rate of synthesis or a decline in the levels as compared with controls. The in vitro and in vivo Rhizobium of Cajanus Cajan plant produced high amount of protein from halophillic glyphosate (Hg) as compared to the Normal (N) plant. The proteomic diversity contributes the variation between the same species; its in vitro and in vivo protein profile contributes the isolated salt and herbicide tolerant Rhizobium sp. produced proteins to adapt in such stress conditions. The possible relationship between the rhizobial protein production & legume rhizobia symbioses related to stress is discussed.